Free Tuition in Chile: A Policy in Foster Care - Bernasconi, Andrés (International Higher Education, 2019)
This article provides an update on Chile’s free tuition policy for higher education, first enacted in 2016. It gives an overview of the political reasons why, currently, there seems to be very little enthusiasm for this policy across academia, political parties, and institutions of higher education. Problems related to the design of this measure contribute to complicating its implementation.